Psychological Beliefs and Financial Wellness in Developing Economy: The Mediating Role of Financial Behavior - Adhikari, Yogendra; Sharma, Rachana (Apex Journal of Business and Management, 2025)
This study investigates the relationship between psychological beliefs and financial wellness in the context of developing economies, specifically focusing on Nepal. It examines how subjective financial knowledge, financial attitudes, and locus of control influence financial wellness, while also assessing the mediating effect of financial behavior. Utilizing a correlational and explanatory research design, data were collected through self-administered questionnaires from 221 financially independent working adults in Nepal. The analysis aimed to identify the associations between psychological beliefs and financial wellness. The findings indicate that positive psychological beliefs—particularly subjective financial knowledge, financial attitudes, and locus of control—are significantly associated with improved financial wellness. While financial behavior mediates the relationship between financial attitudes and financial wellness, it does not mediate the effects of subjective financial knowledge or locus of control. The results underscore the importance of psychological beliefs in shaping financial behavior and overall financial wellness. This study contributes to the limited literature on financial wellness in developing economies and offers valuable insights for policymakers, financial educators, and practitioners. Encouraging financial literacy and fostering positive financial attitudes are essential strategies for enhancing financial wellness among working adults in Nepal. The findings suggest that individuals with sound financial knowledge, a strong sense of control over their finances, and favorable attitudes are better equipped to manage their personal finances effectively.